Journal Series on Governance and Management of IT in Electronic-Based Government Systems (SPBE) in Indonesia - Asianto, Andriyanti; Fatonah, Nenden Siti; Firmansyah, Gerry; Akbar, Habibullah (Jurnal Indonesia Sosial Sains, 2023)
SPBE Governance and Management is a framework that guarantees the implementation of regulation, direction and control in the implementation of SPBE in an integrated manner. SPBE Governance and Management aims to ensure that SPBE elements consist of the National SPBE Master Plan, SPBE Architecture, SPBE Roadmap, SPBE Program Plan and Budget, Business Process, Data and Information, SPBE Infrastructure, SPBE Application, SPBE Security, and Services SPBE. to achieve SPBE goals. In implementing all SPBE elements, integration and harmonization between the National SPBE and Regional SPBE are required. Therefore, this thesis research raises SPBE Governance and Management in accordance with COBIT 2019 as a governance framework that is set globally. Thus, this research will provide recommendations for the implementation of SPBE in Indonesia which can provide appropriate benefits for SPBE users, namely the community, business actors, civil servants, and other government agencies, and have detailed objectives and activities in accordance with COBIT 2019.